2012
DOI: 10.1007/s00404-012-2515-z
|View full text |Cite
|
Sign up to set email alerts
|

Pain relief during hysterosalpingography: role of intracervical block

Abstract: Intracervical block can be offered to all women undergoing HSG to make the procedure less painful and thus improve the compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…The main discomfort during this procedure is during the dye injection due to the stretching of the Fallopian tubes. A recent study [17] evaluated the pain during the different phases of HSG using a VAS scale and they found that the most painful step was dye injection with a mean pain VAS score of 5.12 ± 1.45. This value seems to be quite similar to the result found in this study during the chromopertubation of THL.…”
Section: Discussionmentioning
confidence: 99%
“…The main discomfort during this procedure is during the dye injection due to the stretching of the Fallopian tubes. A recent study [17] evaluated the pain during the different phases of HSG using a VAS scale and they found that the most painful step was dye injection with a mean pain VAS score of 5.12 ± 1.45. This value seems to be quite similar to the result found in this study during the chromopertubation of THL.…”
Section: Discussionmentioning
confidence: 99%
“…International Journal of Reproduction, Contraception, Obstetrics and Gynecology Volume 3 · Issue 1 Page 151 6 Hepburn S. in his study (Method of local anesthesia for IUD insertion) used intracervical block for all IUD insertions. The described technique is simple, low cost, requires no special equipment.…”
Section: Poornima C Et Al Int J Reprod Contracept Obstet Gynecol 20mentioning
confidence: 99%
“…[3][4][5][6] Other researchers have published their experience and proposed analgesia protocols during hysterosalpinography for infertility. [7][8][9] Traditionally, hysterosalpinography for infertility is done under high dye pressure instillation in an attempt to overcome proximal ostial spasm and/or mucus plugs, so hysterosalpinography (HSG) for infertility may be accompanied by pain. 8 In a randomized prospective study, Zhu et al evaluated the effect of warm (37 degrees) versus cold contrast media during hysterosalpinography for infertility in an attempt to reduce reflex tubal/uterine spasm.…”
Section: Introductionmentioning
confidence: 99%
“…8 Chauhan et al similarly attempted to reduce the pain associated with hysterosalpinography for infertility by using an intracervical anesthetic block. 9 Their prospective randomized study divided patients using a computer-generated table into two groups of 50 women each. In the study group, women received an intracervical block along with their premedication, whereas the controls received premedication alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation